Effects of livelihood transformation on older persons in the Nordic Arctic: a gender-based analysis - Begum, Shahnaj (Polar Record, 2015)
ABSTRACT This paper addresses the transformation that has occurred in livelihoods in the Nordic Arctic, showing how it affects gender equality among the region's older people. The region's population includes the Sámi, an indigenous people, who have traditionally relied for their livelihood on activities such as reindeer herding, making handicrafts, farming, fishing, hunting, trapping and gathering. In recent years these have faced enormous challenges because of the rapid transformation of the region in the wake of climate change and globalisation. Overall, these and other processes have precipitated socio-economic, cultural, environmental and infrastructural changes that are transforming the local economies and severely impacting older people in particular. The main research question examined in this article is whether gender inequality has arisen among older people because of the ongoing transformation of livelihoods. To this end, the paper provides an empirical analysis based on experiences gathered from field studies conducted by the author in Finnish and Swedish Lapland. The research also presents the experiences of older persons in light of the standard set by General Recommendation 27 of the Committee on the Elimination of Discrimination against Women, which oversees the United Nations Convention on the Elimination of All Forms of Discrimination Against Women. The Recommendation sets out the right of older women to equality and non-discrimination. The findings of the present research contribute to filling a gap in the literature on the topic.